Uganda's laboratory human resource in the era of global health initiatives: experiences, constraints and opportunities-an assessment of 100 facilities - Suzanne N. Kiwanuka; Noel Namuhani; Martha Akulume; Simeon Kalyesubula; William Bazeyo; Angela N. Kisakye (BMC, 2020)
Abstract Introduction Laboratories are vital in disease diagnosis, prevention, treatment and outbreak investigations. Although recent decades have seen rapid advancements in modernised equipment and laboratory processes, minimal investments have been made towards strengthening laboratory professionals in Africa. This workforce is characterised by insufficient numbers, skewed rural-urban distribution, inadequate qualifications, inadequate skill-mix and limited career opportunities. These factors adversely affect the performance of laboratory professionals, who are the backbone of quality services. In the era of Global Health Initiatives, this study describes the status of laboratory human resource and assesses the experiences, constrains and opportunities for strengthening them in Uganda. Methods This paper is part of a study, which assessed laboratory capacity in 21 districts during December 2015 to January 2016. We collected data using a laboratory assessment tool adapted from the WHO and USAID assessment tool for laboratory services and supply chain (ATLAS), 2006. Of the 100 laboratories, 16 were referral laboratories (hubs). To assess human resource constraints, we conducted 100 key informant interviews with laboratory managers and in charges. Results Across the facilities, there was an excess number of laboratory technicians at Health Center (HC) IV level by 30% and laboratory assistants were in excess by 90%. There was a shortage of laboratory technologists with only 50% of the posts filled at general hospitals. About 87.5% of hub laboratories had conducted formal onsite training compared to 51.2% of the non-hub laboratories. Less than half of HC III laboratories had conducted a formal onsite training; hospital laboratories had not conducted training on the use and maintenance of equipment. Almost all HC III laboratories had been supervised though supervision focused on HIV/AIDS. Financial resources, workload and lack of supervision were major constraints to human resource strengthening. Conclusion Although opportunities for continuous education have emerged over the past decade, they are still threatened by inadequate staffing, skill mix and escalating workload. Moreover, excesses in staffing are more in favour of HIV, TB and malaria. The Ministry of Health needs to develop work-based staffing models to ensure adequate staff numbers and skill mix. Staffing norms need to be revised to accommodate laboratory technologists and scientists at high-level laboratories. Training needs to extend beyond HIV, TB and malaria.